2022
DOI: 10.1155/2022/4969774
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Experience of Diagnosis and Surgical Treatment of 6 Cases of Acute Subhepatic Appendicitis

Abstract: To summarize the experience of diagnosis and surgical treatment of 6 cases of acute subhepatic appendicitis. The clinical data of 6 patients with subacute appendicitis in Zhejiang Provincial People’s Hospital from July 2018 to December 2019 were analyzed retrospectively. Results. There were 5 males and 1 female. All 6 cases were diagnosed as appendicitis by abdominal CT before operation. All patients underwent laparoscopic appendectomy without conversion to laparotomy. One case of ectopic appendix was located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%